Żywność funkcjonalna w Unii Europejskiej - pojęcie, wymagania i rozwój rynku - Korbutowicz, Teresa (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The interest of consumers in maintaining good health and the development of technology increase the importance of functional foods in the food markets. The functional foods themselves have a beneficial effect on health over nutritional value. It is not explicitly defined for the variety of food products included in this category. Undoubtedly the so-called health trend in societies afflicted with civilization diseases (e.g. obesity, diabetes, cardiovascular disease, cancer) has changed the consumer’s attitude towards food. The knowledge about the relationship between quality of food consumption and quality of life, especially a state of health of people was increased. The answer to these trends is the growing number of functional foods that are provided by entrepreneurs. There is also a growing consumption of such food in the world and European countries
Keywords: functional foods; nutrition claims; health claims